A study on the effectiveness of Yayasan Sabah Market News Scan (MNS) for forest products in disseminating market information to it's subscribers / Joy Hardey Javil - Javil, Joy Hardey (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2008)
This project paper is emphasizes on the Yayasan Sabah Market News Scan (MNS) in Sabah. It also aimed to gathering information on their experience, knowledge and satisfaction towards the MNS. The information about Forest Industry in Malaysia and particularly in Sabah is become so important. So that Yayasan Sabah Forestry Division take the opportunity to produce their own Market News about forest product. This study is to know how far this MNS accepted by people especially subscribers. Do the Yayasan Sabah MNS meeting their objectives which is "to gather, collect and disseminating market information including statistics, price, supply, and demand situation of logs and timber products to the forest timber and industries. It is also aimed at promoting market transparency which is one of the core objectives of the International Tropical Timber Agreement (ITT A) 1994".